Riqueza de cupins (Insecta, Isoptera) em uma área de caatinga e outra de cerrado senso restrito na Chapada Diamantina, Bahia, Brasil - Alves, Emerson Almeida (2013)
The current study had as a goal the analysis of termites species in Chapada Diamantina, at two different areas: one through Caatinga and the other at,cerrado restricted sense, Palmiras city, state of Bahia, Brazil and as well as to compare the wealth coming from these organisms considering the physical factors of climate, edaphic and vegetation factors. This study was made at two different areas, the first one in Caatinga and the second place was at cerrado sensu stricto, in Palmeiras city, state of Bahia. there were 12 transects installed for each area studied ( six of them in dry season and the other six in rainy season) which was 65 meters lenght, 2 meters wide and so it owned 5 plots, measuring 5 meters lenght, 2 meters wide, one away from the other 10 meters. There were made soil gathering up to 30 cm depth with the help coming from an 10 cm diameter auger at different spots from each area of study and the analysis of this material was made at the Brazilian Agricultural Research corporation. So, 50 termites species were found belonging to 25 genres, split into three families. The occurance of collected species at Caatinga was slightly richer counting 44 of species, mentioning that 39 from these ones were observed happening at cerrado areas. The results obtained from the curves of accumulation of species through Jacknife estimator first order showed different results as for collection eficiency for both areas. The analysis of wealth variation from both ecosystems and so the analysis of sorting calculated from the Nonmetric Multidimensional Scaling (NMDS) shows a high similarity of species among different studied areas. The results that were here found evidenced from the two studied ecosystems the guild of humivoros as the most meaningful with twenty species showed, however the xylophagous were then the most usual among the samples. The presence of stratum arboreal in both areas may be the determining factor for the finding of these results, as well as for the greatest wealth of termite species at Caatinga, cause the presence of greenery may promote important resources offer for these insects survival.